Prognostic implications of fibroblast growth factor receptor 4 polymorphisms in primary breast cancer. Issue 8 (16th April 2018) - Wei, Wei; You, Zilong; Sun, Shanshan; Wang, Yuhang; Zhang, Xianyu; Pang, Da; Jiang, Yongdong
Abstract : Fibroblast growth factor receptor 4 (FGFR4) belongs to the receptor tyrosine kinase (RTK) family, and FGFR4 polymorphisms have been implicated in both normal development and cancer, including breast cancer. In the present study, we investigated correlations between polymorphisms in FGFR4 and breast cancer prognosis. The FGFR4 SNPs rs1966265 and rs351855 were genotyped in 747 breast cancer patients using the SNaPshot method. FGFR4 protein expression was detected by immunohistochemistry in 339 samples. SNP rs351855 was correlated with FGFR4 protein expression under dominant and co‐dominant models. Lymph node metastasis (LNM), ER (estrogen receptor) status, and molecular subtype were associated with high FGFR4 expression. Univariate analysis revealed rs351855 (CC/CT: P  = 0.027, CC/TT: P  <  0.001, CC/CT + TT: P  = 0.005) to be a prognostic predictor, and multivariate analysis indicated rs351855 (CC/TT: P  = 0.005) to be an independent prognostic factor. Kaplan‐Meier survival analysis showed that high FGFR4 protein expression was associated with a poor prognosis. SNP rs351855 was correlated with worse outcomes, with a dose‐dependent effect. The results of this study show that FGFR4 SNP rs351855 is associated with up‐regulation of FGFR4 protein expression and a worse prognosis in breast cancer.